Performance of Lambs Born to Energy- and Protein-Supplemented Ewes During Gestation and Lactation - Silva, N. C.; Cabral Filho, S. L. S.; Freitas, I. O. M. A.; Rocha, F. C.; Azevedo, A. M.; Rocha Júnior, V. R.; Ribeiro, M. D. (Tropical Animal Science Journal, 2026)
Maternal nutrition and supplementation during gestation and lactation improve fetal development, survival, and growth of lambs. The aim of this study was to evaluate the effects of energy and protein supplementation in the diet before, during, and in the final third of gestation and lactation, within a synchronized breeding system, on the health and performance of lambs. Forty Santa Inês × Dorper ewes, averaging ten months of age and two previous births, were distributed in a completely randomized design with four treatments: mineral supplementation only, supplementation initiated before breeding, supplementation starting after pregnancy confirmation, and supplementation restricted to late gestation. Supplements were provided daily at 4 pm at 1% of body weight (BW), adjusted every 15 days when ewes were weighed. The experimental period lasted 60 days, with 10 days of adaptation. Variance analysis was performed in subdivided plots, and the means were compared using Tukey's test at 5% probability. Concentrated supplementation altered (p